The first record of the crustacean isopod genus Pseudarachna Sars, 1897 (Isopoda: Asellota: Munnopsidae) from the Southern Hemisphere, with description of a new species from New Zealand - Merrin, Kelly L. (Zootaxa, 2006)
Pseudarachna nohinohi n. sp. from the Challenger Plateau, New Zealand is described. A further two undescribed species are recorded from Australian waters in the Tasman Sea, showing that this formerly monotypic North Atlantic genus is more widely distributed than previously thought. A revised diagnosis of the genus is presented.